Immunosensor development for rice tungro bacilliform virus (RTBV) detection using antibody nano-gold conjugate - Uda, Muhammad Nur Aiman; Che Man, Hasfalina; Abd Aziz, Samsuzana; Hashim, Uda; Ariffin, Shahrul Aizzam; Ishak, Zamri; Wahid, Nur Sabrina; Bunawan, Siti Noraini; Salam, Faridah; Mat, Mazidah; Gopinath, Subash Chandra Bose (AIP Publishing, 2015)
Rice tungro disease (RTD) causes major losses to rice crop plantation. Hence, a highly sensitive tools need to be developed for the detection of RTD which can be employed in both laboratory and field. An electrochemical immunosensor system for the detection of RTD, based on immobilized specific antibodies conjugated with gold nanoparticle was developed for this purpose. However, this paper focus for RTBV interaction using the conjugated antibodies which is added with polymer and deposited on carbon screen printed working electrodes.